Care in a birth center according to the recommendations of the World Health Organization - Flora Maria Barbosa da Silva; Tais Couto Rego da Paixao; Sonia Maria Junqueira Vasconcellos de Oliveira; Jaqueline Sousa Leite; Maria Luiza Gonzalez Riesco; Ruth Hitomi Osava (SciELO, 2013)
Birth centers are maternal care models that use appropriate technology when providing care to birthing women. This descriptive study aimed to characterize intrapartum care in a freestanding birth center, in light of the practices recommended by the World Health Organization (WHO), with 1,079 assisted births from 2006 to 2009 in the Sapopemba Birth Center, São Paulo, Brazil. Results included the use of intermittent auscultation (mean=7 controls); maternal positions during delivery: semi-sitting (82.3%), side-lying (16.0%), other positions (1.7%), oral intake (95.6%); companionship (93.3%); exposure to up to three vaginal examinations (85.4%), shower bathing (84.0%), walking (68.0%), massage (60.1%), exercising with a Swiss ball (51.7%); amniotomy (53.4%), oxytocin use during the first (31.0%) and second stages of labor (25.8%), bath immersion (29.3%) and episiotomy (14.1%). In this birth center, care providers used practices recommended by the WHO, although some practices might have been applied less frequently.